Pyometra in Queens - Changes in Haemato-Biochemical Parameters - Satilmis, Fatma (Acta Scientiae Veterinariae, 2023)
Background: Pyometra is a bacterial and hormone-induced reproductive disease that occurs in the post-estrus luteal phase in intact queens. Pyometra is more common in the diestrus period due to the high progesterone concentration (in queens that mated, spontaneously ovulated, or were induced to ovulate). However, it can also be seen due to the use of exogenous hormones such as progesterone for the suppression of estrus. More research is needed in cases of pyometra in queens, as well as in bitches. Because, considering that the pathogenesis and characteristics of feline pyometra is similar to bitches, studies on pyometra-affected bitches are taken as reference in studies and applications on queens. From this point of view, the aims of this study were to reveal the changes in complete blood count, blood gas, and serum biochemistry parameters in feline pyometra cases and to determine the correlation between the mentioned parameters. Materials, Methods & Results: In the study, a total of 25 female cats of different breeds were used, between the ages of 6 months and 7 years, 15 were diagnosed with pyometra, and 10 healthy. Anamnesis, clinical findings, and ultrasonographic examinations were used in the diagnosis of pyometra. Abdominal ultrasonography was performed on queens brought to the clinic with complaints such as anorexia, polydipsia, polyuria, abdominal tension, and fever. The control group (n =10) consisted of queens that were introduced to the clinic and were reproductively healthy. Before any treatment in queens with pyometra and the control group, 1 mL blood samples were taken from v. cephalica to evaluate complete blood count, blood gases and serum biochemistry parameters. In complete WBC, Lym, Mon, Gra, RBC, Hb, HCT, MCV, MCH and PLT parameters and, blood gas parameters such as pH, pCO2, pO2, sO2, Na, K, Cl, lactate, glucose, HCO3, and BE were also evaluated in taken blood samples. Biochemical parameters BUN, creatinine, ALT, AST, ALP, amylase, T.BIL, D.BIL, P, CHOL, TG, LDH, TP, CPK, ALP, Ca, GGT were measured in serum samples. After examination and laboratory analysis, ovariohysterectomy was performed on queens as a treatment. Granulocyte, WBC, HCT and MCH levels of the pyometra group were higher (P < 0.05) and Lym levels were lower (P < 0.05) compared to the control group. According to these results, pH, HCO3, and BE were lower (P < 0.05) in queens with pyometra than those in the control group, while Na and lactate parameters were higher (P < 0.05). According to the results of biochemical analysis, it was determined that BUN, creatinine levels, GGT, and LDH enzyme activities were found to be higher in the pyometra group compared to the control group, while the Ca level was found to be low (P < 0.05). A positive correlation was observed between BUN and creatinine and LDH, WBC, granulocyte, HCT, and lactate, and a negative correlation between lymphocytes, pH, and BE in the correlation analysis performed on queens with pyometra and control group. However, a positive correlation was observed between creatinine and LDH and HCT, and a negative correlation between lymphocyte, pH and BE. Discussion: There is not enough information about pyometra in queens. As a result, it was determined that there were significant changes in complete blood count, blood gases and serum biochemical parameters in queens with pyometra in this study. These changes were generally thought to be related to dehydration and sepsis or endotoxemia. In addition, it was evaluated that prerenal azotemia occurring in pyometra affected queens may cause renal dysfunction. For this reason, it is thought that the results obtained in the presented study may contribute to the diagnosis, treatment, and prognosis of pyometra cases in queens. Keywords: female cats, blood gas analysis, complete blood count, correlation, serum biochemistry.